(untitled) (diségno, 2021)
In the Murcia Cathedral there is an important repertoire of vaulted systems showing very refined structures and decorations which were built with stereotomic technique. The painter and architect Jacopo Torni (1476-1526) and the essayist Alonso de Vandelvira (1544-1626) are some of the personalities who were involved in it. This paper focuses on the drawings published in Vandelvira’s treatise and analyses in detail two uncommon case studies in the field of this construction technique: the Capilla de Junteron’s vault and the one covering the room of the anti-sacristy. A digital restitution of the case studies will then be offered, with the aim of highlighting the geometric genesis of their stone joint through the intersection between architectural volumes and fundamental geometric entities. The contribution is also intended to investigate the relationship among stereotomy, astrolabes and cartography. We would like hypothesizing how the tools for the observation and calculation of celestial phenomena (astrolabes and planispheres) may have been assumed as inspiring models for the subdivision into blocks of some vaulted surfaces. Celestial and terrestrial maps, assumed as projections on the plane of spatial models, could therefore have indirectly influenced the history of constructions through a logic of subdivision into blocks that would have solved the problem of the development of the sphere on the plane according to cartographic logics, or by approximating meridians and parallels to portions of ruled surfaces.